O meio rural da Quarta Colônia de imigração italiana como tema e cenário turístico - Nardi, Oni (2007)
The present dissertation is a result of a research accomplished along with the Post-Graduate Program in Geography and Geociences of UFSM, which had as general goal the analysis of touristic scenaries throughout the rural environment in the Fourth Colony of Italian Imigration Region of Rio Grande do Sul (RQCII). The Fourth Colony Region situated in the geographical center of Rio Grande do Sul between the coordinates 29° 09 15 to 29° 58 37 of south latitude and 53° 47 18 to 53° 59 13 of west longitude, has constituted itself as the fourth and last colonial core created by the imperial government to settle italian imigrants within Rio Grande do Sul. The colonization began in 1877 by settling north-italian migrational waves from the Venetian region, which originated seven small rural municipalities: Silveira Martins, Nova Palma, Ivorá, Faxinal do Soturno, Dona Francisca, São João do Polêsine and Pinhal Grande. The socioeconomical functionality of the region is determined by familial agricultural activities, sustained by a populacional contingent of 29.779 inhabitants who still maintain colonial bonds that originated them, and live predominantly in rural environments. Thanks to colonial heritage and low development gained, the region is characterized by its conservancy of great historical- cultural and landscape riches, determined by territoriality built through the lifestyles of the first imigrants, identified by habits (dances, rites, foods, clothes, linguistic dialects, religion, crafts etc), understood as living memory of forefathers. Today these peculiarities generate interest in people who search within local identitary culture a refuge from standarized patterns brought on by cultural globalization. Facing the potentials present within its territory and the crisys that has permeated the agricultural sector, specialy in the 1990 s, the Region has emprehended sistematic efforts towards a rescue and valuation of its ethnic-cultural and socioeconomical identity. The regional singularity has come to be seen as different and, consequently, awaken as touristic scenarie, what has been the main factor of recent reorientation of the rural environment. The study uses the sistemic methodology allowing caracterization, classification and analysis of its scenaries to tourism of rural environment of agricultural regions. The main results achieved by the investigation indicate the rural environment is being seen as a place that combines quality of life and leisure with the strong identitary culture, where colonization has produced intrinsic peculiarities. Currently, this Colonial Region presents itself as authentic, identitary and diferent, before the standarized and globaly determined cultural ideals, what generates curiosity and atracts tourists, contributing to socioeconomical reproduction, in face of the contemporary crisis and (re)valoring the rural territory.